1993
DOI: 10.1111/j.1432-1033.1993.tb18017.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of type IV collagen with the isolated integrins α1β1 and α2β1

Abstract: The triple-helical cyanogen-bromide-derived fragment CB3 [IV] of collagen IV, located 100 nm from the N-terminus of the molecule, contains the binding sites for the integrins alp1 and a2pl. To investigate the interaction of these integrins and collagen IV, we performed solid-phase and inhibition assays using as receptor isolated alp1 and a2pl. The ligands used were the binding-site-bearing trimeric peptide CB3 [IV] and its shorter tryptic fragments Fl-F4. Using titration curves, in which the binding of solubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
188
0
2

Year Published

1994
1994
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(208 citation statements)
references
References 47 publications
18
188
0
2
Order By: Relevance
“…These two integrins bind both collagen IV and collagen I, however, with distinct specificity as follows: integrin α 1 β 1 has a higher affinity for collagen IV, while α 2 β 1 binds stronger to collagen I (Kern et al, 1993;Tulla et al, 2001a). It was shown that deletion of α 1 β 1 integrin by the homologous recombination resulted in dramatic decrease in adhesion and migration of fibroblasts and smooth muscle cells to collagen IV substrate (Gardner et al, 1996), while the importance of α 2 β 1 integrin was demonstrated by the decrease of adhesion and morphogenesis on collagen IV after using antisense mRNA (Keely et al, 1995).…”
Section: Integrin Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…These two integrins bind both collagen IV and collagen I, however, with distinct specificity as follows: integrin α 1 β 1 has a higher affinity for collagen IV, while α 2 β 1 binds stronger to collagen I (Kern et al, 1993;Tulla et al, 2001a). It was shown that deletion of α 1 β 1 integrin by the homologous recombination resulted in dramatic decrease in adhesion and migration of fibroblasts and smooth muscle cells to collagen IV substrate (Gardner et al, 1996), while the importance of α 2 β 1 integrin was demonstrated by the decrease of adhesion and morphogenesis on collagen IV after using antisense mRNA (Keely et al, 1995).…”
Section: Integrin Receptorsmentioning
confidence: 99%
“…By affinity chromatography using immobilized CB3 fragments and cellular lysates, α 1 β 1 and α 2 β 1 were isolated as the only integrins eluted from the affinity column (Vandenberg et al, 1991). Using purified integrins and shorter tryptic fragments of CB3, one binding site for α 1 β 1 integrin and two for α 2 β 1 integrin were located in different but adjacent positions on CB3 fragment (Kern et al, 1993). Further refinement of the α 1 β 1 recognition site was achieved by digestion of one of the tryptic peptides with thermolysin .…”
Section: Integrin Receptorsmentioning
confidence: 99%
“…EHS, Engelbreth-Holm-Swarm. Kern et al, 1993), and a3pl Sonnenberg et al, 1991). EHS tumor laminin-1 also possesses a cryptic RGD site which is recognized by pl and p3 integrins, although their corresponding a chains have not been firmly identified (Aumailley et al, 1990b;1991).…”
mentioning
confidence: 99%
“…6 -8). Five laminin-binding integrins of the ␤1 family recognize different sites and isoforms of laminin: ␣6␤1 (9, 10) and ␣7␤1 (11,12) bind to laminin-1, recognizing specifically the E8 domain; ␣1␤1 binds to a cryptic site in the E1 region of laminin (13), but also to types I and IV collagen (14). The ␣3␤1 integrin binds to laminin-5 (kalinin) (15) and to other matrix proteins; ␣2␤1 is predominantly a collagen receptor (16), but when isolated from endothelial cells it also binds to laminin-1 (17).…”
mentioning
confidence: 99%